2009
DOI: 10.1093/jnci/djp037
|View full text |Cite
|
Sign up to set email alerts
|

Total and Cancer Mortality After Supplementation With Vitamins and Minerals: Follow-up of the Linxian General Population Nutrition Intervention Trial

Abstract: The beneficial effects of selenium, vitamin E, and beta-carotene on mortality were still evident up to 10 years after the cessation of supplementation and were consistently greater in younger participants. Late effects of other supplementation regimens were also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
210
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(227 citation statements)
references
References 49 publications
11
210
2
4
Order By: Relevance
“…Vitamin A and zinc supplementations were associated with a higher total and cerebrovascular mortality. These findings which were similar to the findings of 5 year follow-up, are also important in showing the durability of the beneficial effects of some antioxidants after a long time [221].…”
Section: Cancersupporting
confidence: 88%
“…Vitamin A and zinc supplementations were associated with a higher total and cerebrovascular mortality. These findings which were similar to the findings of 5 year follow-up, are also important in showing the durability of the beneficial effects of some antioxidants after a long time [221].…”
Section: Cancersupporting
confidence: 88%
“…Although selenium did not protect participants from the development of additional skin cancers, selenium supplementation was associated with a nearly 40% reduction in total cancer incidence, particularly in prostate cancer. The Linxian General Population Nutrition Intervention Trial found that a combination of selenium, vitamin E, and b-carotene reduced overall mortality as well as cancer rates (Blot et al 1993;Qiao et al 2009).…”
Section: Clinical Trials Of Antioxidants In Cancer Preventionmentioning
confidence: 99%
“…It is important to emphasize adequate nutrition, as calorie restriction associated with malnutrition can potentially increase cancer incidence [301][302][303]. Consequently, consumption of foods containing the active groups of respiratory enzymes (iron salts, riboflavin, nicotinamide, and pantothenic acid) could be effective in maintaining health when combined with dietary energy restriction [25].…”
Section: Implications Of the Hypothesis To Cancer Preventionmentioning
confidence: 99%